Entoação e produção de sentidos no discurso do sujeito parkinsoniano - Dantas, Sônia de Sousa (2006)
The study of pronunciation, particularly of intonation, is gaining space in the field of language research on language aquisition and development Intonation patterns used in interaction studies are in close relation with studies in the field of discourse, offering a wide field for research. The present study aimed to, analyse the relation of intonation with the production of senses in the discourse of patients with Parkinson disease. The data used was collected from patients that integrate the Association of Parkinsonians, from individual interviews, answering to questions and talking about their difficulties and life projects. Concious that interactional studies consider intonation as one of the strategies of which the speaker makes use to guide the listner to apprehend the comunicative meaning of what is said, it was observed, throughout the analysis of data that the parkinsonian patient, ahead of a classical, evolutional and limitative sintomatology, presents alterations in the use of intonational patterns, by using tha intonational neutral pattern and the intonational descending one. The tone chains and tone units were also very segmented, generating a monotonous dialogue, and without colorful phonetic thus compromising its communicative intention, and as a consequence, the production of senses in speech, affeting the interactional process. The present study outlined the intonation profile of the patients here described, with the intention of contributing for new therapeutical clinical ways, supporting the patients with Parkinson s disease, by providing a better interactive quality of life